2015
DOI: 10.1590/0101-60830000000066
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary rehabilitation program: effects of a multimodal intervention for patients with Alzheimer’s disease and cognitive impairment without dementia

Abstract: Background: Non-pharmalogical interventions represent an important complement to standard pharmalogical treatment in dementia. Objective: This study aims to evaluate the effects of a multidisciplinary rehabilitation program on cognitive ability, quality of life and depression symptoms in patients with Alzheimer's disease (AD) and cognitive impairment without dementia (CIND). Methods: Ninety-seven older adults were recruited to the present study. Of these, 70 patients had mild AD and were allocated into experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
0
33
0
9
Order By: Relevance
“…Recent data from our research programme has shown, in particular, that multidisciplinary therapy increases grey matter volume in the caudate tail and dorsolateral PFC in patients with manifest HD (147). This therapy has also been reported to improve cognitive function, quality of life and depressive symptoms in patients with mild AD and cognitive impairment without dementia (148) and in PD, multidisciplinary therapy has been reported to improve motor performance, dyskinesias, balance and gait and slow disease progression (149)(150)(151). The molecular mechanisms driving these neural and clinical changes are yet to be investigated.…”
Section: Effects Of Multidisciplinary Therapy On Brain Volume and Potmentioning
confidence: 88%
“…Recent data from our research programme has shown, in particular, that multidisciplinary therapy increases grey matter volume in the caudate tail and dorsolateral PFC in patients with manifest HD (147). This therapy has also been reported to improve cognitive function, quality of life and depressive symptoms in patients with mild AD and cognitive impairment without dementia (148) and in PD, multidisciplinary therapy has been reported to improve motor performance, dyskinesias, balance and gait and slow disease progression (149)(150)(151). The molecular mechanisms driving these neural and clinical changes are yet to be investigated.…”
Section: Effects Of Multidisciplinary Therapy On Brain Volume and Potmentioning
confidence: 88%
“…Assim, um total de cinco artigos foram incluídos e descritos no presente estudo [18][19][20][21][22] . As razões para exclusão dos demais estudos foram: não eram experimentais, não realizaram uma intervenção multidisciplinar ou não eram pacientes com Os estudos foram sumarizados na Tabela 1, sendo três ensaios controlados 18,19,22 , um ensaio clínico aleatorizado 20 e um quase aleatorizado 21 , com qualidade metodológica média de 5,4 pontos na escala PEDro (variação de 4 a 7) (Tabela 2). Todos os estudos foram realizados com amostra de conveniência e incluíram 576 participantes, com idade média de 77,7 anos, dos quais 236 eram homens.…”
Section: ▄ Resultadosunclassified
“…Dois estudos incluíram pacientes com DA leve 21,22 , um estudo incluiu pacientes com DA avançada 20 e dois deles não especificaram a fase da doença em que os participantes se encontravam 18,19 . Apesar de os tratamentos terem como foco principal a multidisciplinaridade, três estudos não citaram os profissionais envolvidos, embora relatassem a aplicação de um protocolo multidisciplinar 18,21,22 . Dos demais estudos, as modalidades profissionais incluídas nas equipes multiprofissionais foram: enfermeiro, médico (neurologista), psicólogo e fisioterapeuta.…”
Section: ▄ Resultadosunclassified
See 1 more Smart Citation
“…Therefore, the ToM TB must be considered as an alternative for these populations, since the tool proposes to assess the theory of mind at different levels of linguistic and cognitive capacity. In addition, researches with cognitive rehabilitation programs have pointed to improvement in several cognitive domains 8 without assessment of social cognition, so the ToM TB could be used in intervention studies to evaluate this important domain.…”
mentioning
confidence: 99%